The Influence of Work Environment, Organizational Culture, and Work Discipline on Employee Performance at PUD Pasar Kota Medan - Olivia Umma Enelis; Yohny Anwar; Ikhah Malikhah (Universitas Dehasen Bengkulu, 2026)
This study aimed to examine the effect of the work environment, human resource development, and work discipline on employee performance at PUD Pasar Kota Medan. The population in this study consisted of 760 employees, with a sample of 89 employees determined using the Slovin formula. The sampling technique used was purposive sampling. This study was conducted in 2026. The research used quantitative primary data collected through the distribution of questionnaires and then processed using SPSS 24.0 with a multiple linear regression analysis model. The results showed that the work environment, organizational culture, and work discipline, both partially and simultaneously, had a positive and significant effect on employee performance at PUD Pasar Kota Medan. Work discipline became the most dominant variable affecting employee performance, with a regression value of 0.595 and a t-value of 5.566. Approximately 91.8% of employee performance could be explained by the work environment, organizational culture, and work discipline, while the remaining portion was influenced by other factors. Employee performance had a very strong relationship with the work environment, organizational culture, and work discipline, as indicated by an R value of 0.960.